Abduction and Contraction for Semantic-Based Mobile Dating in P2P Environments - Ruta, Michele; Noia, Tommaso Di; Sciascio, Eugenio Di; Scioscia, Floriano (Proceedings of the 2008 IEEE/WIC/ACM International Conference on Web Intelligence and Intelligent Agent Technology - Volume 01, 2008)
In a generic semantic-based matchmaking process, given a request, it is desirable to obtain a ranked list of compatible services/resources/profiles in order of relevance. Furthermore, a match explanation can provide useful information to modify or refine the original request in a principled way. Though the feasibility of such an approach has been proved with fixed reasoning engines, it is a challenging subject to perform inference tasks on handheld devices. Here we propose abduction and contraction algorithms in Description Logics specifically devised for applications in mobile environments. A simple interaction paradigm based on Bluetooth protocol stack has also been implemented and tested in a mobile dating case study.